Analysis of Atomization Performance of Linear Laval Nozzle under Varied Water Pressures Based on VOF and DPM Models - Shanshan, Tang; Mohd Danial, Ibrahim; Andrew Ragai, Henry Rigit; Wei, Zhang; Chaokun, Wei (Taiwan Association of Engineering and Technology Innovation., 2024)
Particulate matter from coal and stone operations is a primary air pollution source. The traditional nozzle requires high-pressure conditions, and the atomization droplets are large and uneven. This paper aims to study a linear Laval nozzle and investigate the impact of water pressure on atomization performance. The volume of fluid (VOF) model and discrete phase model (DPM) of Fluent are used to simulate the internal and external fields of the nozzle and analyze the velocity, droplet size, and atomization angle. The results show that the optimized water pressure parameters are 0.1 MPa with an air pressure of 0.5 MPa. Droplets in the middle are smaller, while those on the sides are larger. Compared to traditional nozzles, the water pressure is reduced by over 90%, and the Sauter mean diameter (SMD) decreases by over 50%. Moreover, the theoretical spray angle increases by approximately 150%.